Nieznane rękopisy 12 nieopusowanych pieśni Jerzego Gablenza ze zbiorów Biblioteki Narodowej - Mikolon, Anna (Musica Galiciana. Kultura muzyczna Galicji w kontekście stosunków polsko-ukraińskich, 2023)
Jerzy Gablenz’s vocal legacy (1888–1937) includes over 80 songs. Most of them were ordered in opuses 3, 4, 5, 7, 9, 10, 11, 13, 16, 18, 19, 21, 28 and rewritten by Thomas Gablenz, translating the text into English. Few manuscripts are in the National Library, where they were probably donated in 1974 (before the death of the composer’s widow). However, in this library’s collection, there are 12 other songs that the composer’s son does not mention, which he did not copy and include in his catalog of works. These are: From Hania IX, I feel sad on the ground, Zosia, Lonely lime, For water, Girl, Where are you going, Scherzo, From poems II, Circular, In a foreign country and unfinished Bills once. It is possible to read the date 1986 on yellowed sheets of sheet music. The article aims to present the results of their analysis.